U–Pb (LA-ICP-MS) ages on detrital zircon grains from Angacos limestone siliciclastic levels (Caucete Group), San Juan province, Argentina: provenance implications for the Cuyania terrane - Naipauer, Maximiliano (2005)
In this work, we present isotopic results on detrital zircon grains in siliciclastic levels from Angacos Limestone. This unit, together with the El Quemado, La Paz and El Desecho Formations, constitute the Caucete Group (Borrello, 1969; emend. Vujovich, 2003), which occurs on the western side of the Pie de Palo range in northwestern Argentina (Fig. 1). The Pie de Palo Complex is bordered by the Las Pirquitas Thrust and is characterized by Grenville-age basement with medium- to high-grade metamorphic and minor igneous rocks (Vujovich et al., 2004, and references therein). The Pie de Palo range is part of the Cuyania composite terrane (Ramos et al., 1998) and has been recognized as an allochthonous microcontinent derived from Laurentia or as paraautochthonous unit from Gondwana (Finney et al., 2005). The Angacos Limestone is mainly composed of limestone, calcareous schist, dolostone, and calcitic marble. The metamorphism indicates greenschist facies (Ramos and Vujovich, 2000). Moreover, mylonitic products of the high deformation that affected the entire zone are present. The protolith of these carbonates is interpreted as a succession of limestone and dolostone with minor sandstone interbeds. The age of the Angacos Limestone is uncertain because of the absence of diagnostic fossils. Isotopic studies of Sr, C and O has led to the correlation with the Early Paleozoic platform limestone sequence from the Precordillera (Linares et al., 1982; Galindo et al., 2004; Naipauer et al., 2005). It is important to note that the El Quemado Formation as a part of the Caucete Group has a maximum depositional age of 550 Ma as defined by detrital zircon data (Naipauer et al., 2005). The main purpose of this work is to present isotopic data of the detrital zircons separated from siliciclastic levels interlayered within the Angacos Limestone. We compare the obtained results with detrital zircon data from the El Quemado Formation (Naipauer et al., 2005; Ellis, 2005), and discuss some provenance implications in the tectonic terrane.